Methodology for Completing Test Tasks of Different Degrees of Complexity in the Computer Graphics Display (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
Increasing the effectiveness of education in the process of teaching computer graphics lies in organizing the educational process using new information and communication technologies, as well as monitoring the quality of mastering units of the educational module. Taking this into account, the article theoretically analyzes the methodology for creating test questions in computer graphics and a number of related graphic disciplines. It has been determined that factor theory is related to graphic sciences. As a result, the structure of a system of three-level test tasks based on specific formulas and their coefficients was studied. In addition, a four-category student assessment system was tested using a general automated software tool for questionnaire control. Based on the results, a mathematical and statistical analysis was carried out and the range of variation of the four categories was shown.